Teachers’ Perception of the Adoption of Digital Technologies for E-learning during Covid-19 Pandemic in Nigeria - Santas, Tsegyu; Udende, Patrick; Inobemhe, Kelvin; Modeyin, Oluwatobi (Journal of Education Method and Learning Strategy, 2025)
Covid-19 took the world by surprise, resetting world events for most of 2020. The educational system was negatively affected as students were forced to remain at home for several months without receiving teacher instructions. To engage the students remotely, most schools adopted e-learning to facilitate instructions so that the students would not waste their academic time to the pandemic. E-learning became a platform to ensure teachers connect with their students outside the classrooms. This study occurred among three purposively selected schools in Keffi Local Government Area Council of Nasarawa State, Nigeria. This research aimed to assess teachers’ perceptions of adopting digital technologies in giving instructions during the pandemic. Findings from the study show that digital technologies were quite valuable and beneficial to the teachers in providing instructions to the students. Further findings reveal that even though digital technologies proved helpful in providing instruction to the students, teachers faced challenges like unstable power supply, high cost of purchasing data and distractions from family members and friends. The study, among others, recommends that government and private individuals invest heavily in infrastructure to enable teachers to be better equipped to give instructions via digital media technologies.